Employee well-being in international business travel : A case study from a global business context - Teliö, Emma (My University, 2026)
This thesis examines employee well-being in the context of international business travel. It addresses the following research question: “How do employees experience well-being across the different phases of international business travel?” International business travel remains an important part of work in many international organisations, and previous research has shown that it may affect employee well-being in several ways. Building on this literature, this study aims to explore employee well-being across the pre-trip, during-trip, and post-trip phases of international business travel. The theoretical framework of this study positions international business travel within the con-text of internationalisation and examines employee well-being across different phases, in relation to travel stress, cultural differences, and organisational support. The study was conducted as a qualitative case study at a global SME. The empirical data were collected through thematic interviews with employees whose work involves 20-180 days of international business travel per year. Afterwards, the data was analysed thematically to identify recurring experiences related to well-being in different phases of travel. The findings show that employee well-being is shaped by phase-specific demands, stressors, and recovery challenges. In the pre-trip phase, well-being is affected by scheduling and coordination uncertainty, booking and logistical planning demands, lack of shared knowledge, cost and time pressure and the need to balance work and personal life before departure. During the trip, employees experience stress related to long working days, intensive schedules, disrupted routines, cultural and communication challenges, and limited opportunities for rest and recovery. In the post-trip phase, well-being is influenced by fatigue, backlog of work and the need to adjust both work and private life. The findings further suggest that within the company, international business travel is experienced as a recurring cycle rather than a set of isolated events, as demands arising before, during, and after travel often overlap and shape employee well-being across phases. The study contributes to the literature on international business travel by using a phase-based case study approach to examine employee well-being across pre-trip, during-trip, and post-trip travel. In this process, it builds on existing theories and research on internationalisation, travel stress, cultural differences, and HRM support.

Tämä tutkielma tarkastelee työntekijöiden hyvinvointia kansainvälisen liikematkustuksen kontekstissa. Tutkimus vastaa seuraavaan tutkimuskysymykseen: “Miten työntekijät kokevat hyvinvoinnin kansainvälisen liikematkustuksen eri vaiheissa?” Kansainvälinen liikematkustaminen on edelleen tärkeä osa työntekoa monissa kansainvälisissä organisaatioissa, ja aiempi tutkimus on osoittanut sen vaikuttavan työntekijän hyvinvointiin monin tavoin. Aiempien tutkimusten pohjalta tämän tutkielman tavoitteena on tarkastella työntekijöiden hyvinvointia kansainvälisen liikematkustuksen eri vaiheissa, eli ennen matkaa, matkan aikana, ja matkan jälkeen. Tutkimuksen teoreettinen viitekehys sijoittaa kansainvälisen liikematkustuksen kansainvälistymisen kontekstiin ja tarkastelee työntekijöiden hyvinvointia eri vaiheissa suhteessa matkustamisesta aiheutuvaan stressiin, kulttuurisiin eroihin ja organisaation tarjoamaan tukeen. Tutkimus toteutettiin kvalitatiivisena tapaustutkimuksena globaalisti toimivassa pk-yrityksessä. Empiirinen aineisto kerättiin teemahaastattelujen avulla työntekijöiltä, joiden työ sisälsi 20-180 päivää kansainvälistä liikematkustamista vuodessa. Tämän jälkeen aineisto analysoitiin temaattisesti toistuvien hyvinvointiin liittyvien kokemusten tunnistamiseksi matkan eri vaiheissa. Tutkimustulokset osoittavat, että työntekijöiden hyvinvointiin vaikuttavat matkustuksen eri vaiheisiin asettuvat vaatimukset, kuormitustekijät ja palautumiseen liittyvät haasteet. Ennen matkaa hyvinvointiin vaikuttavat aikatauluihin ja koordinointiin liittyvä epävarmuus, varausten ja logistiikan suunnitteluun liittyvät vaatimukset, keskitetyn tiedon puuttuminen, kustannus- ja aikapaineet sekä työn ja yksityiselämän yhteensovittamisen tarve ennen lähtöä. Matkan aikana työntekijät kokevat kuormitusta pitkien työpäivien, intensiivisten aikataulujen, häiriintyneiden rutiinien, kulttuuristen ja kommunikaatioon liittyvien haasteiden, sekä rajallisen lepo- ja palautumismahdollisuuksien vuoksi. Matkan jälkeisessä vaiheessa hyvinvointiin vaikuttavat väsymys, matkan aikana työtehtävien kasaantuminen sekä tarve sopeuttaa työ ja yksityiselämä uudelleen matkan jälkeen. Tulokset viittaavat lisäksi siihen, että kansainvälinen liikematkustaminen koetaan yrityksessä jatkuvana syklinä, jossa ennen matkaa, matkan aikana ja matkan jälkeen ilmenevät vaatimukset, kuormitustekijät ja palautumiseen liittyvät haasteet limittyvät ja vaikuttavat työntekijöiden hyvinvointiin eri vaiheissa. Tutkielma täydentää kansainvälistä liikematkustusta koskevaa tutkimusta tarkastelemalla työntekijöiden hyvinvointia ennen matkaa, matkan aikana ja matkan jälkeen tapaustutkimuksen kautta. Tutkimus pohjautuu aiempaan kirjallisuuteen ja teoreettisiin näkökulmiin, jotka liittyvät kansainvälistymiseen, matkustusstressiin kulttuurisiin eroihin ja henkilöstöjohtamisen tukeen.
Keywords: employees; well-being; business trips; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business